2021
DOI: 10.1038/s41598-021-93950-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal monitoring of laboratory markers characterizes hospitalized and ambulatory COVID-19 patients

Abstract: Early detection of severe forms of COVID-19 is absolutely essential for timely triage of patients. We longitudinally followed-up two well-characterized patient groups, hospitalized moderate to severe (n = 26), and ambulatory mild COVID-19 patients (n = 16) at home quarantine. Human D-dimer, C-reactive protein (CRP), ferritin, cardiac troponin I, interleukin-6 (IL-6) levels were measured on day 1, day 7, day 14 and day 28. All hospitalized patients were SARS-CoV-2 positive on admission, while all ambulatory pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…A longitudinal study showed that levels of inflammatory cytokines remained elevated in severe COVID-19 cases but declined within days in patients with moderate disease [ 39 ]. The cytokine IL-6 was shown to be a valuable biomarker of COVID-19 severity and an indicator of viral load [ 40 , 41 ].…”
Section: The Immunology Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…A longitudinal study showed that levels of inflammatory cytokines remained elevated in severe COVID-19 cases but declined within days in patients with moderate disease [ 39 ]. The cytokine IL-6 was shown to be a valuable biomarker of COVID-19 severity and an indicator of viral load [ 40 , 41 ].…”
Section: The Immunology Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…We found that plasma levels of CHI3L1 were reduced in COVID-19 survivors four weeks after clinical remission, at a time when systemic inflammation had returned to baseline levels 25 . Interestingly, CHI3L1 levels at this point were still significantly higher than in healthy subjects, suggesting that stimuli sustaining CHI3L1 production are still present.…”
Section: Discussionmentioning
confidence: 69%
“…To the best our knowledge, so far neither longitudinal data on troponin changes for (out)patients with non-severe COVID-19 have been reported; nor have reports included longitudinal observations for more than 1 year in comparison to a control cohort ( 6 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that increased troponin levels in patients with severe ( 1 ) COVID-19 are associated with an increased likelihood of cardiovascular disease, critical illness ( 2 , 3 ), and death ( 4 , 5 ). Patients with COVID-19 not only show troponin levels above the 99th percentile more frequently, but also show measurably increased levels of troponins (below the 99th percentile but above the limit of detection) more frequently ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%